Farside - Bova, Ben, 1932-2020 (Tor, 2013)
"The discovery of an Earth-sized planet 30 light years from Earth sparks a race to develop a telescope to create a photographic record of the new world. The far side of the moon, with its "clear" view of space, seems an ideal location, but the project's planners must contend with rivalries from the existing moon colony of Selene. Sent from Earth to assist Dr. Ulrich, director of Angel Observatory, Dr. Trudy Yost immediately becomes involved in the web of politics, sabotage, and physical obstacles that mark life on Farside."--Library Journal.